Phân tích đa thức thành nhân tử : 4(2x + 10)(2x + 12)(x + 10)(x + 12)
Phân tích đa thức thành nhân tử : 4(x + 5)(x + 6)(x + 10)(x + 12) + 3x2
Đa thức này không phân tích được thành nhân tử.
Bạn coi lại đề.
Ta có: \(4\left(x+5\right)\left(x+6\right)\left(x+10\right)\left(x+12\right)+3x^2\)
\(=4\left(x^2+60+17x\right)\left(x^2+60x+16x\right)+3x^2\)
\(=4\left[\left(x^2+60\right)^2+33x\left(x^2+60\right)+272x^2\right]+3x^2\)
\(=4\left(x^2+60\right)^2+132x\left(x^2+60\right)+1091x^2\)
Phân tích đa thức thành nhân tử : x^4 - 2x^3 + 2x - 1
\(x^4-2x^3+2x-1=x^3\left(x-1\right)-x^2\left(x-1\right)-x\left(x-1\right)+\left(x-1\right)=\left(x-1\right)\left(x^3-x^2-x+1\right)=\left(x-1\right)\left[x^2\left(x-1\right)-\left(x-1\right)\right]=\left(x-1\right)^2\left(x^2-1\right)=\left(x-1\right)^3\left(x+1\right)\)
\(x^4-2x^3+2x-1\)
\(=\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)\)
\(=\left(x-1\right)^3\cdot\left(x+1\right)\)
Phân tích đa thức thành nhân tử : x^4 + 2x^3 + x^2 + x + 1
\(=x^2\left(x^2+2x+1\right)+x+1\)
\(=x^2\left(x+1\right)^2+x+1\)
\(=\left(x+1\right)\left[x^2\left(x+1\right)+1\right]\)
\(=\left(x+1\right)\left(x^3+x^2+1\right)\)
\(x^4+2x^3+x^2+x+1\)
\(=x^2\left(x+1\right)^2+\left(x+1\right)\)
\(=\left(x+1\right)\left(x^3+x^2+1\right)\)
Phân tích đa thức thành nhân tử : 5x^2 - 4(x^2 - 2x + 1) - 5
\(5x^2-4\left(x^2-2x+1\right)-5=\left(5x^2-5\right)-4\left(x-1\right)^2=5\left(x^2-1\right)-4\left(x-1\right)^2=5\left(x-1\right)\left(x+1\right)-4\left(x-1\right)^2=\left(x-1\right)\left[5\left(x+1\right)-4\left(x-1\right)\right]=\left(x-1\right)\left(5x+5-4x+4\right)=\left(x-1\right)\left(x+9\right)\)
\(= \)\(5x^2-4x^2+8x-4-5\)
\(=\)\(x^2+8x-9\)
\(=x^2+9x-x-9\)
\(=(x-1)(x+9)\)
\(5x^2-4\left(x^2-2x+1\right)-5\)
\(=5x^2-4x^2+8x-4-5\)
\(=x^2+8x-9\)
\(=\left(x+9\right)\left(x-1\right)\)
Phân tích đa thức thành nhân tử : (x2 + x)2 + 4x2 + 4x – 12
\(\left(x^2+x\right)^2+4x^2+4x-12=\left[\left(x^2+x\right)^2+4\left(x^2+x\right)+4\right]-16=\left(x^2+x+2\right)-4^2=\left(x^2+x+2-4\right)\left(x^2+x+2+4\right)=\left(x^2+x-2\right)\left(x^2+x+6\right)=\left(x-1\right)\left(x+2\right)\left(x^2+x+6\right)\)
\(\left(x^2+x\right)^2+4x^2+4x-12\\ =\left(x^2+x+2\right)-4\\ =\left(x^2+x-2\right)\left(x^2+x+6\right)\)
\(\left(x^2+x\right)^2+4x^2+4x-12\)
\(=\left(x^2+x+6\right)\left(x^2+x-2\right)\)
\(=\left(x^2+x+6\right)\left(x+2\right)\left(x-1\right)\)
phân tích đa thức thành nhân tử
a) x^3+4x^2-7x-10
b) x^2+2x-y^2+1
c)(x^2+x)^2+4(x^2+x)-12
b, x2-2x-y2+1
=(x-1)2-y2
(HĐT số 2)
=(x-y-1)(x+y-1)
(HĐT số 3)
c, (x2+x)2+4(x2+x)-12
=(x2+x)2+4(x2+x)+4-16
=(x2+x+2)2-16 (HĐT số 1)
=(x2+x+2-4).(x2+x+2+4)
(HĐT số 3)
=(x2+x-2).(x2+x+6)
=(x2+2x-x-2) .(x2+x+6)
=(x+2).(x-1). (x2+x+6)
a, x3+4x2-7x-10
=x3-2x2+6x2-12x+5x-10
=x2(x-2) + 6x(x-2)+5(x-2)
=(x-2)(x2+6x+5)
=(x-2)(x2+5x+x+5)
=(x-2)(x+5)(x+1)
Phân tích đa thức thành nhân tử : (x + y)2 + 3(x + y) – 10
\(\left(x+y\right)^2+3\left(x+y\right)-10=\left[\left(x+y\right)^2+2\left(x+y\right).\dfrac{3}{2}+\dfrac{9}{4}\right]-\dfrac{49}{4}\)
\(=\left(x+y+\dfrac{3}{2}\right)^2-\dfrac{49}{4}=\left(x+y+\dfrac{3}{2}-\dfrac{7}{2}\right)\left(x+y+\dfrac{3}{2}+\dfrac{7}{2}\right)=\left(x+y-2\right)\left(x+y+5\right)\)
\(\left(x+y\right)^2+3\left(x+y\right)-10\)
\(=\left(x+y\right)^2+5\left(x+y\right)-2\left(x+y\right)-10\)
\(=\left(x+y+5\right)\left(x+y-2\right)\)
Phân tích đa thức thành nhân tử
x4+x3+2x2+x+1
\(x^4+x^3+2x^2+x+1\)
\(=\left(x^4+2x^2+1\right)+\left(x^3+x\right)\)
\(=\left(x^2+1\right)^2+x\left(x^2+1\right)\)
\(=\left(x^2+1\right)\left(x^2+1+x\right)\)
x^4+x^3+2x^2+x+1
=(x^4+2x^2+1)+(x^3+x)
=(x^2+1)^2+x(x^2+1)
=(x^2+1)(x^2+x+1)
phân tích đa thức thành nhân tử :
x^3 - 3x^2 - 4x +12
\(x^3-3x^2-4x+12\)
\(=x^2\left(x-3\right)-\left(4x-12\right)\)
\(=x^2\left(x-3\right)-4\left(x-3\right)\)
\(=\left(x^2-4\right)\left(x-3\right)\)
\(=\left(x+2\right)\left(x-2\right)\left(x-3\right)\)
\(x^3-3x^2-4x+12\)
\(=x^2\left(x-3\right)-4\left(x-3\right)\)
\(=\left(x^2-4\right)\left(x-3\right)\)
\(=\left(x+2\right)\left(x-2\right)\left(x-3\right)\)